Hepatotoxicity of anabolic androgenic steroids in sport - Sekuła, Michał Jakub; Świerczyńska, Blanka; Smoluchowski, Krzysztof; Undziakiewicz, Adrian; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Anabolic-androgenic steroids (AAS) abuse is a common practice among professional as well as recreational athletes. The prevalence of this phenomenon seems to be continuously escalating, too. Even though AAS abuse may provide a desirable haematopoietic and musculotrophic effect, it causes a wide variety of local and systemic side effects. This review aims to demonstrate the AAS induced hepatotoxicity, it is based on the medical literature from the last 10 years. Brief description of the state of knowledge: Orally administered 17-α-alkylated steroids are considered to be the most hepatotoxic. They increase the number of reactive oxygen species (ROS) which directly injure the liver tissue. It may be manifested as an elevation of liver enzymes, peliosis hepatis or distinctive acute cholestasis. Furthermore, ASS abuse for a prolonged period of time may induce the growth of hepatocellular adenoma and hepatocellular cancer. Moreover, AAS intake can lead to liver enlargement, development of toxicant-associated fatty liver disease (TAFLD) and increase the risk of HCV and HBV infection. Conclusions: The collaboration of scientists, doctors, sports associations and governments is substantial. Introduction of innovative AAS detection methods and enforcement of stricter anti doping law may contribute to prevention of health consequences resulting from AAS abuse among athletes.